(untitled) (Libellarium: journal for research in the field of information and related sciences, 2017)
Technical and industrial heritage are very important parts of cultural heritage. Their preservation faces many challenges. One of them is certainly the safekeeping of documentation that is often disconnected from the specific industrial and technical artefacts. Documentation in the context of industrial heritage represents all written, printed and electronic documents related to the specific industry and all documentation created as a result of industrial processes. Technical documentation represents all documents that describe or are related to the specific technical object. Long-term preservation and accessibility of industrial and technical heritage documentation faces many challenges. The aim of this paper is to bring focus to preservation of industrial and technical heritage documentation and to give insight into the challenges of doing research of these issues in Croatia.